2019
DOI: 10.1194/jlr.m093799
|View full text |Cite|
|
Sign up to set email alerts
|

FTY720/fingolimod decreases hepatic steatosis and expression of fatty acid synthase in diet-induced nonalcoholic fatty liver disease in mice

Abstract: Supplementary key words lipogenesis • sphingolipids • sphingosine-1phosphateNonalcoholic fatty liver disease (NAFLD) encompasses a spectrum of disease states defined by hepatic steatosis occurring in the absence of alcohol abuse (1). Steatosis is the initial stage of NAFLD, in which lipid droplets form and accumulate in the liver (2). This stage can be self-limiting; however, steatosis can progress to more aggressive liver injury, inflammation, and fibrosis in the form of nonalcoholic steatohepatitis (NASH) (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 80 publications
0
35
0
Order By: Relevance
“…[13] FTY720 inhibited expression of the cytokines that have been shown to play a role in liver fibrosis in the mice model of diet-induced non-alcoholic fatty liver disease while FTY720 only had a minimal effect on inflammation. [14] Early administration of FTY720 inhibited the severity and fibrosis in murine sclerodermatous chronic GvHD through decreasing soluble collagen and dermal thickness. [15] In a recent study, FTY720 was found to directly and specifically target various phenotypes of hypertrophic scarring fibroblasts (HSFs), suppressing the expression of fibrotic markers such as α-smooth muscle actin (α-SMA) and collagen, effectively suppressing HSF activation [16].…”
Section: Introductionmentioning
confidence: 99%
“…[13] FTY720 inhibited expression of the cytokines that have been shown to play a role in liver fibrosis in the mice model of diet-induced non-alcoholic fatty liver disease while FTY720 only had a minimal effect on inflammation. [14] Early administration of FTY720 inhibited the severity and fibrosis in murine sclerodermatous chronic GvHD through decreasing soluble collagen and dermal thickness. [15] In a recent study, FTY720 was found to directly and specifically target various phenotypes of hypertrophic scarring fibroblasts (HSFs), suppressing the expression of fibrotic markers such as α-smooth muscle actin (α-SMA) and collagen, effectively suppressing HSF activation [16].…”
Section: Introductionmentioning
confidence: 99%
“…The BMI in MS modulates ceramide-induced DNA methylation and disease course, via increased levels of monocytes [78]. Gut-derived butyrate is significantly decreased in obesity, and is an important driver of the alterations in the gut–liver axis that underpin obesity, non-alcoholic fatty liver disease, and wider metabolic dysregulation [79], all of which may be suppressed by fingolimod, suggesting unrecognized gut microbiome, butyrate/HDAC inhibitory-like effects of this drug [80,81].…”
Section: Ms Pathophysiologymentioning
confidence: 99%
“…Other data on MS pathophysiology may also be framed within this model, including the role of ceramide and gut dysbiosis in glucose dysregulation, insulin resistance, and the lipid alterations that are common in MS [148], with ceramide decreasing high-density lipoprotein (HDL) cholesterol and increasing very low-density lipoprotein (vLDL) cholesterol [149]. This model also provides a framework for incorporating the effects of medication in the treatment of MS, e.g., fingolimod inhibits aSMase and ceramide [80], including ceramide-induced emergent obesity in MS [150], and, like butyrate, increases gangliosides via HDAC inhibitory effects [85]. Although they have optimizing effects in mitochondria, orexin and melatonin can have distinct and sometimes opposing effects on glia and immune cells [151,152], which seems to contribute to the circadian variation in glia and immune cell activity [153].…”
Section: Integrating Ms Pathophysiologymentioning
confidence: 99%
“…Targeting S1PRs was shown to be a promising strategy for treating NASH after the recent preclinical success of FTY720 16 , a drug for multiple sclerosis 17 . FTY720 (Fingolimod; 2-amino-2-[2-(4-noctylphenyl)ethyl]-1, 3-propanediol hydrochloride), a non-selective modulator of S1PRs (S1PR1, 3, 4, and 5), has been shown to prevent the development of alcoholic liver disease 18 , NAFLD 19 and NASH 16 in murine models. However, a widespread use of FTY720 in NASH has been hampered by its lymphopenic effects.…”
Section: Introductionmentioning
confidence: 99%